Infectious diseases in primates behavior, ecology and evolution - Nunn, Charles L.; Altizer, Sonia M. (Oxford Oxford University Press, 2006)
An advanced textbook suitable for graduate level students as well as professional researchers in the fields of behavioural ecology, primatology, conservation biology, biological anthropology, public health and wildlife epidemiology.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Primates -- Infections; Primates -- Behavior; Primates -- Ecology; Primates -- Parasites; Primates -- Diseases -- Epidemiology; Electronic books; Electronic books